Acceptance and willingness to pay for a hypothetical vaccine against monkeypox viral infection among frontline physicians: A cross-sectional study in Indonesia. Issue 43 (7th October 2020) - Harapan, Harapan; Wagner, Abram L.; Yufika, Amanda; Setiawan, Abdul M.; Anwar, Samsul; Wahyuni, Sri; Asrizal, Febrivan W.; Sufri, Muhammad R.; Putra, Reza P.; Wijayanti, Nanda P.; Salwiyadi, Salwiyadi; Maulana, Razi; et al.
Abstract: Background: A clinical trial is ongoing to evaluate the safety and efficacy of a monkeypox vaccine among healthcare workers (HCWs). The critical question that needs to be addressed is whether HCWs are willing to accept and purchase this vaccine. The objective of this study was to evaluate the acceptance and willingness to pay (WTP) for the vaccine among HCWs. Methods: From May to July 2019, a cross-sectional study was conducted among registered general practitioners (GPs) in Indonesia. A contingent valuation method was employed to evaluate the WTP. Besides acceptance and WTP, various explanatory variables were also collected and assessed. A logistic regression and a multivariable linear regression were used to explore the explanatory variables influencing acceptance and WTP, respectively. Results: Among 407 respondents, 391 (96.0%) expressed acceptance of a free vaccination. The mean and median WTP was US 37.0 (95%CI: US 32.76–US 41.23) and US 17.90 (95%CI: US 17.90–US 17.90), respectively. In an unadjusted analysis, those 30 years old or younger had 2.94 times greater odds of vaccine acceptance compared to those who were older (95%CI: 1.07–8.08). Location of alma mater, type of workplace, length of individual medical experience, and monthly income of GPs were all significantly associated with WTP. Conclusion: Although the vast majority of GPs would accept a freely provided vaccine, they were also somewhat price sensitive. This finding indicates that partial subsidy maybe required to achieve high vaccine coverage, particularly among GPs at community health centres or those with a shorter duration of medical practice.